Perioperative Skin Preparation and Draping in Modern Total Joint Arthroplasty: Current Evidence. - Markatos, Konstantinos; Kaseta, Maria; Nikolaou, Vasileios S (Surg Infect (Larchmt), 2015)
BACKGROUND: Besides the vast success and reliability of lower extremity joint replacement, deep and periprosthetic infection remains a serious complication of such operations. Many publications addressing periprosthetic infection have remarked about this "devastating" complication, with a risk around 1% after total hip arthroplasty and between 1% and 2% after total knee arthroplasty. The purpose of this study is to assess current trends in prevention of contamination with improved up-to-date pre-operative skin preparation methods and intra-operative draping. METHODS: A literature review was conducted in MEDLINE, Web of Science, and the Cochrane database, looking for high-quality papers summarizing the most widely held and up-to-date concepts of perioperative measures for reducing infection, focusing on the best available evidence concerning skin preparation for joint arthroplasty (THR and THR) and surgical draping. RESULTS: Current evidence suggests the use of alcohol solutions for pre-operative painting with emphasis on the use of chlorhexidine gluconate solutions beginning the night before surgery. Hair removal should be performed in the operating room with electric clippers, not razor blades. In order to enhance drape adhesion to the skin, the use of iodophor-in-alcohol solutions is recommended over the traditional scrub-and-paint technique. Disposable non-woven drapes are superior to reusable woven cotton/linen drapes in resisting bacterial penetration. Finally, the use of adherent plastic adhesive incision drapes for the prophylaxis of post-operative surgical site infections is considered not necessary in orthopedic surgery. CONCLUSIONS: The importance of skin preparation and adequate and reliable draping cannot be overemphasized for infection prevention, especially in clean operations such as THR and TKR. Thorough and strict protocols are mandatory for every department, as well as education curricula for operating room personnel. Further randomized studies are mandatory to specify the effect of the above measures, their pitfalls, and their improvement, along with further crucial details such as cost-benefit analysis of different pre-operative preparations in preventing infections.
Keywords: Arthroplasty, Replacement, Hip; Arthroplasty, Replacement, Knee; Disinfection; Humans; Preoperative Care; Surgical Wound Infection